Determinan Pernikahan Dini Di Kecamatan Pakis Kabupaten Magelang - Ambarwati, Nur Aini; Rohmayanti, R (Prosiding University Research Colloquium, 2021)
Background: Indonesia is ranked second in ASEAN countries with the highest marriage after Cambodia. The percentage of early marriages in Magelang Regency is 22%. Pakis subdistrict ranked first in early marriage with 55% of married men aged 19-25 years old and 39% of married women aged 16-19 years old. Objective: The general objective of this study is to determine the determinants of early marriage and the most dominant factors in Kecamatan Pakis, Magelang district. Method: This study used a case control method. The number of samples were 50 respondents, 25 case groups and 25 control groups. The sampling technique used proportional random sampling with Chi Square statistical tests and logistic regression. This study used a questionnaire. Results: Chi Square test results showed variables that have a relationship with early marriage, namely education (p = 0,000), employment (p = 0.005), media (p = 0.009), knowledge (p = 0.001), democratic parenting (p = 0.037 ). While those who had no relationship with early marriage are economics (p = 0.1380), social culture (p = 0.254), level of religiosity (p = 0.569), authoritarian parenting (p = 0.069), and permissive parenting (p = 1,000). The logistic regression test results showed that education and employment variables have the most dominant relationship with early marriage. Conclusion: Factors related to early marriage in Pakis Subdistrict are education, employment, media, knowledge and democratic parenting. Suggestion: this research is expected to increase public knowledge about the determinants of early marriage in order to avoid or minimize young marriage.